An actively decoupled dual transceiver coil system for continuous ASL at 7 T. Issue 2 (June 2016) - Stafford, Randall B.; Woo, Myung‐Kyun; Oh, Se‐Hong; Dolui, Sudipto; Zhao, Tiejun; Kim, Young‐Bo; Detre, John A.; Cho, Zang‐Hee; Lee, Jongho
ABSTRACT: 7 T arterial spin labeling (ASL) faces major challenges including the increased specific absorption rate (SAR) and increased B0 and B1 inhomogeneity. This work describes the design and implementation of a dual‐coil system that allows for continuous ASL (CASL) at 7 T. This system consisted of an actively detunable eight‐channel transceiver head coil, and a three‐channel transceiver labeling coil. Four experiments were performed in 5 healthy subjects: (i) to demonstrate that active detuning during ASL labeling reduces magnetization transfer; (ii) to measure the B1 profile at the labeling plane; (iii) to quantify B0 off‐resonance at the labeling plane; and (iv) to collect in vivo CASL data. The magnetization transfer ratio in the head coil was reduced to 0.0 ± 0.2% by active detuning during labeling. The measured B1 profiles in all 5 subjects were sufficient to satisfy the flow‐driven adiabatic inversion necessary for CASL, however the actual labeling efficiency was significantly impacted by B0 off‐resonance at the labeling plane. The measured CASL percent signal change in gray matter (0.94% ± 0.10%) corresponds with the low labeling efficiency predicted by the B0 off‐resonance. This work demonstrates progress in the technical implementation of 7 T CASL, and reinforces the need for improved B0 homogeneity at the labeling plane.